Testing the rotation versus merger scenario in the galaxy cluster Abell 2107. Issue 3 (12th March 2019) - Liu, Ang; Tozzi, Paolo
ABSTRACT: We search for global rotation of the intracluster medium in the galaxy cluster Abell 2107, where previous studies have detected rotational motion in the member galaxies with a high-significance level. By fitting the centroid of the iron K α line complex at 6.7–6.9 keV rest frame in Chandra ACIS-I spectra, we identify the possible rotation axis with the line that maximizes the difference between the emission-weighted spectroscopic redshift measured in the two halves defined by the line itself. Then, we measure the emission-weighted redshift in linear regions parallel to the preferred rotation axis, and find a significant gradient as a function of the projected distance from the rotation axis, compatible with a rotation pattern with maximum tangential velocityv_max=1380± 600 km s −1 at a radius λ0 ∼ 160 kpc. This result, if interpreted in the framework of hydrostatic equilibrium, as suggested by the regular morphology of Abell 2107, would imply a large mass correction of the order ofΔ M = (6 ± 4)× 10^13 M_ at ∼160 kpc, which is incompatible with the cluster morphology itself. A more conservative interpretation may be provided by an unnoticed off-centre, head-on collision between two comparable haloes. Our analysis confirms the peculiar dynamical nature of the otherwise regular cluster Abell 2107, but is not able to resolve the rotation versus merger scenario, a science case that can be addressed by the next-generation X-ray facilities carrying X-ray bolometers on board.